An Innovative Calcium Looping Process as Energy Storage System Integrated With a Solar-Powered Supercritical CO2 Brayton Cycle - Cannone, Salvatore F.; Lanzini, Andrea; Stendardo, Stefano (Frontiers in Sustainability, 2021)
Coupling solar thermal energy with the hybrid TC/CG-ES (Thermo-Chemical/Compressed-Gas Energy Storage) is a breakthrough option used to overcome the main challenge of solar energy, i.e., intermittent resource, low density. This paper proposes an innovative storage system that improves the competitiveness of solar thermal energy technologies compared to conventional fossil-based power plants, potentially leading to deep decarbonization of the energy and industrial sectors. This study uses thermo-chemical energy storage based on the Calcium Looping (CaL) process and takes advantage of a number of factors: high energy density (2 GJ/m3), absence of heat loss (seasonal storage), high operation temperature (high efficiency of the power plant) and use of cheap and environmentally friendly reactant feedstock (CaO/CaCO3). The main components of the system are: (i) a new solar calciner able to directly harvest sunlight by decomposing calcium carbonate in calcium oxide (CaO) and carbon dioxide (CO2) and (ii) a carbonator where CaO and CO2 are recombined together, releasing heat at high temperatures (>600 °C). This work deals with the integration of the solar CaL storage system with an unconventional supercritical-CO2 (s-CO2) Brayton cycle. We analyze different s-CO2 Brayton cycle layouts suitable for direct integration with the storage system. Energy integration via pinch analysis methodology is applied to the whole system to optimize the internal heat recovery and increase the system's efficiency. A parametric study highlights how the integration of solar CaL with an inter-cooling Brayton cycle shows better results than the combination with the Rankine cycle that we investigated previously, resulting in net and global system efficiencies equal to 39.5% and 51.5%. Instead, the new calculated net and global system efficiencies are 44.4% and 57.0%, respectively for TC-CG-ES coupled with the Brayton power cycle.